Evolving Toolbox for Complex Project Management - Gorod, Alex; Hallo, Leonie; Ireland, Vernon; Gunawan, Indra (New York : Auerbach Publications, 2019)
This book enhances learning about complex project management principles and practices through the introduction and discussion of a portfolio of tools presented as an evolving toolbox. Throughout the book, industry practitioners examine the toolsets that are part of the toolbox to develop a broader understanding of complex project management challenges and the available tools to address them. This approach establishes a dynamic, structured platform for a comprehensive analysis and assessment of the modern, rapidly changing, multifaceted business environment to teach the next generation of project managers to successfully cope with the ever increasing complexity of the 21st century.
Foreword Preface Acknowledgments Editors Contributors Chapter 1 Introduction to the Evolving Toolbox Alex Gorod and Leonie Hallo Chapter 2 Case Studies Toolset Brian E. White Chapter 3 Scheduling Toolset Seyed Ashkan Zarghami and Alex Gorod Chapter 4 Cost Estimation Toolset Ricardo Valerdi Chapter 5 Human Factors Toolset Alicia Aitken Chapter 6 Leadership Toolset Thomas Grisham Chapter 7 Systemic Negotiation and Conflict Resolution Toolset Barbara Rapaport, Kaye Remington, and Alon Ben-Meir Chapter 8 Organization and Systems Theory Toolset Joana Geraldi, Josef Oehmen, Christian Thuesen, and Pedro Parraguez Ruiz Chapter 9 Enterprise Governance Toolset Charles B. Keating and Polinpapilinho F. Katina Chapter 10 Critical Success Factors and Climate Toolset Azadeh Rezvani and Neal M. Ashkanasy Chapter 11 Pattern Identification and Management Toolset Robert Cloutier Chapter 12 Policy Management Toolset George L. De Feis and Dolores A. Atallo Chapter 13 Legal Aspects Toolset George F. Jergeas Chapter 14 Intellectual Property Toolset Alexey Bakman Chapter 15 Systems Thinking Toolset Michael Emes and David Cole Chapter 16 Test and Evaluation Toolset Keith Joiner, Mahmoud Efatmaneshnik, and Malcolm Tutty Chapter 17 Advanced Visualization Toolset Thomas A. McDermott Chapter 18 Social Network Analysis Toolset Kon Shing Kenneth Chung Chapter 19 Modeling and Simulation Toolset Sergey Suslov and Dmitry Katalevsky Chapter 20 Adaptability, Agility, and Resilience Toolset Nil H. Kilicay-Ergin Chapter 21 Cyber-Systemic Toolset Fredmund Malik and Nam Nguyen Chapter 22 Systemic Risk Toolset: Another Dimension Fran Ackermann Chapter 23 Systemic Innovation Toolset Gerrit Muller, Kristin Falk, and Marianne Kjørstad Index
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Project Management; COMPUTERS / Information Technology; TECHNOLOGY / Engineering / General; Project management; Organizational change